Robo2 is required for Slit-mediated intraretinal axon guidance - Thompson, Hannah (Elsevier, 2009)
The developing optic pathway has proven one of the most informative model systems for studying mechanisms of axon guidance. The first step in this process is the directed extension of retinal ganglion cell (RGC) axons within the optic fibre layer (OFL) of the retina towards their exit point from the eye, the optic disc. Previously, we have shown that the inhibitory guidance molecules, Slit1 and Slit2, regulate two distinct aspects of intraretinal axon guidance in a region-specific manner. Using knockout mice, we have found that both of these guidance activities are mediated via Robo2. Of the four vertebrate Robos, only Robo1 and Robo2 are expressed by RGCs. In mice lacking robo1 intraretinal axon guidance occurs normally. However, in mice lacking robo2 RGC axons make qualitatively and quantitatively identical intraretinal pathfinding errors to those reported previously in Slit mutants. This demonstrates clearly that, as in other regions of the optic pathway, Robo2 is the major receptor required for intraretinal axon guidance. Furthermore, the results suggest strongly that redundancy with other guidance signals rather than different receptor utilisation is the most likely explanation for the regional specificity of Slit function during intraretinal axon pathfinding.